Moljac . The Moth - Milošević, Milivoje Mića (TRZ Film i Ton ; Union Film, 1984)
Dedicated to a famous Serbian theater actor and to his popular role, this film is a genuine example of Yugoslav mainstream comedy, filled with populist humor. The film tells the comic story of an actor who becomes over-involved in his role. Miodrag Andrić is a divorced national theatre star who tours the country playing a character named “Moth”. The play is popular, but the trouble is that everybody takes him for his theatrical character. Burdened by this popularity and numerous entertainment duties, and further troubled by his teenage son who wants to cash in on his father’s popularity, he starts losing his way, and in the process gets into a series of comic situations. Gradually he too gets so engrossed in his role that he starts believing that he is actually becoming a character from his act, the “Moth”, so he seeks professional help. Unfortunately, the doctor turns out to be even worse psychopath than Miodrag himself. In order to escape from his theater role, he quits acting and starts doing various different jobs, only to realize that he does not know to do anything except tell jokes.